Epoxidation of jatropha methyl esters via acidic ion exchange resin: optimization and characterization - Derahman, Aishah; Zainal Abidin, Zurina; Cardona, Francisco; Awang Biak, Dayang Radiah; Md. Tahir, Paridah; Abdan, Khalina; Liew, Kan Ern (Springer, 2019)
Plant oils and their derivatives have been vigorously exploited as alternatives for synthesis of epoxides due to depletion of petroleum resources. In this study, crude jatropha oil (CJO) was subjected to a transesterification process to form jatropha methyl esters (JME) using peroxyacetic acid generated in situ from hydrogen peroxide and acetic acid via an acidic ion exchange resin (AIER). The effect of temperature, molar ratio of hydrogen peroxide to unsaturation, molar ratio of acetic acid to unsaturation, and catalyst loading were investigated. This study revealed that the maximum 89.9% relative conversion to oxirane rings was achieved after 6 h with the optimal reaction conditions of temperature at 70 ˚C, the molar ratio of hydrogen peroxide to unsaturation of 1.5 mol, the molar ratio of acetic acid to unsaturation of 0.5 mol, and catalyst loading of 16%. Fourier Transform Infrared (FTIR) spectra of the epoxidized jatropha methyl esters (EJME) showed oxirane peaks (doublet) at 825 and 843 cm-1.1H NMR confirmed the diepoxide group at 2.85 ppm and 2.98 ppm, while the diepoxide signals of 1C NMR were present at 56.88-57.06 ppm. Production of bio-epoxides from Jatropha methyl esters hence looks promising with favorable physicochemical properties, availability, and versatility.